Histopathological and molecular characterization of Ustilaginoidea virens in rice - R.K. SHARMA, POOJA KUMARI* and (Indian Phytopathology, 2017)
Histopathological studies of false smut balls on rice spikelet were conducted through SEM and microtomy. Detection and identification of the fungal culture of Ustilaginoidea virens from infected host tissue was done through polymerase chain reaction (PCR) using U. virens specific internal transcribed spacer (ITS) primer. The primer amplified 380bp product.